The European Union deforestation-free policy and the potential impacts on the Brazilian economy: the soy supply chain case - Stam, Heloiza Prazeres da Silva (2024)
The European Union implemented a pioneering law aimed at ensuring deforestation-free supply chains for various commodities. This paper explores the implications of this policy on the Brazilian soy supply chain, examining contrasting perspectives from industry associations and environmental organizations. The objective is to estimate the economic impact of the European Union Deforestation-Free Regulation (EUDR), utilizing a multiregional Computable General Equilibrium model to analyze variations across Brazilian regions and changes in land use. A dynamic model was used to simulate the impact on the Brazilian economy until 2030. Without the disclosed risk classification list, three policy scenarios are run. These scenarios compare with the baseline projection, reflecting historical trends. Policy Scenario 1 (1AMZN) increases costs just in the regions in the Amazon biome, Scenario 2 (2AMZCER) similar to one but includes regions in Amazon plus Cerrado biomes, and Scenario 3 (3ALL) for all regions exporting to the European Union. The goal is to highlight EUDR\'s impact on Brazilian economic growth under different risk classifications. The results showed a multifaceted impact on the Brazilian economy and emissions. Key findings include a potential reduction in deforestation, aligning with the regulation\'s objectives, but with a minor negative impact on national GDP and currency devaluation. Notably, middle-class households may face reduced consumption capacity due to wage reductions, raising concerns about their overall quality of life. The research indicates a shift in cultivation towards alternative crops, such as coffee, corn, orange, rice, and wheat, as viable substitutes for soybean production, but does not completely offset the reduction in soybean production and exports. Regionally, the impact varies, with Mato Grosso and Rondonia expected to be most negatively affected aggravating regional economic inequality. While emissions are projected to decrease in most regions, Mato Grosso, Rondonia, MaToPi, and ParaAP may experience an increase due to pasture emissions from ranching as an alternative to soy production. Economic downturns are predicted for MaToPi and Bahia, areas with increased agricultural production and substantial forest land. The impact increased progressively from 1AMZN, to 2AMZCER, and in 3ALL, however scenarios 2AMZCER and 3ALL had similar values with nuanced differences that indicate the inclusion of Cerrado biome would have the same effect as classifying the whole country as high-risk.